(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2024)
Newcastle disease (ND) now seems endemic in commercial poultry industry of Bangladesh with continuous significant high prevalence and regular outbreaks. High morbidity, up to 100% mortality rate and high economic loss of ND makes it major constraints of poultry industries. We find out the prevalence of ND in dead, sick and apparently healthy poultry at Bogura district of Bangladesh. From July 2020 to June 2021, we observed a total of 500 birds including 31 sick and dead birds randomly from 10 commercial poultry farms of Bogura district. The prevalence was assessed through clinical observations and the documented history of individual birds. For pathological analysis, 31 samples from sick and deceased birds were collected, and detailed examinations of gross lesions and histopathological changes in the cecal tonsils and proventriculus were conducted. Wide ranges of clinical signs are observed in affected birds and it can be diagnosed based on clinical signs and pathological studies. The prevalence of Newcastle disease was 14.20% in apparently healthy birds and 26.6% in sick and dead birds. ND prevalence increased in summer (56%) and decreased in rainy season (11.5%) and highest at the age group of (5-36) weeks of age. Grossly, numerous infected birds had lesions such as pin-point hemorrhage on proventriculur gland, hemorrhage in the trachea, congested and consolidated lungs, button-like ulcers in the caeca, and hemorrhagic caecal tonsils. Microscopically, there was hemorrhage in the lamina propria associated with lymphatic nodules of the caecal tonsil, sloughing of glandular epithelial cells and infiltration of inflammatory cells in the lumen of the proventriculur gland, congestion around the lobule of the proventriculus, and hyperemia on glandular epithelial cells of the proventriculur gland. This research revealed Newcastle disease remains endemic in Bangladesh’s poultry industry, causing high prevalence, seasonal outbreaks, and severe economic losses. Asian Australas. J. Biosci. Biotechnol. 2024, 9(3), 45-55